Rainy Days Based on a Novel by Yoon Heung-gil - Yu Hyun-mok; Yu Young-gil; Hwang Jeong-soon; Lee Dae-geun; Kim Shin-jae (Korean Film Archive, 2009)
Told through the eyes of a child, "Rainy Days" is a poignant drama about a family torn apart by the Korean War. Dong Man's uncle on his father's side fights for the North, and his uncle on his mother's side died fighting for the South. The war and ideologies that divide the nation have also divided the household, leading to constant fighting among his grandmothers and other family members. Amid a wave of deaths, the family finds a moment of peace and reconciliation from an unlikely visitor. Starring Hwang Jung Seun, Lee Dae Keun, and Kim Sin Jae. [www.yesasia.com]
Keywords: DVD-Video